Accounting Controls and Quality of Financial Reporting - Olumoh, Yusuf Alabi (Copernican Journal of Finance & Accounting, 2025)
This research objective of the study is to examine the impacts of accounting controls on the quality of financial reporting within microfinance banks (MFBs) located in Kwara State, Nigeria. A cross-sectional survey methodology was utilized in this research, involving a total of 216 stakeholders from all 27 licensed MFBs. The study drew upon primary data obtained from a selected group of 140 stakeholders within the MFB industry in Kwara State, Nigeria, utilizing random and stratified sampling methods. The data analysis was conducted using descriptive and inferential statistics employing the Partial Least Square Structural Equation Modelling technique. The results of the study reveal that both detective and corrective controls have a significant positive effect on the financial reporting quality of MFBs in the area, while preventive controls do not exhibit a significant impact on financial reporting quality at a 5% level of significance. This study concludes that accounting controls, particularly corrective and detective controls, play a crucial role in enhancing the quality and reliability of financial reporting in microfinance banks, while the impact of preventive controls remains less significant, with insights into the implications of these findings and offers recommendations for improving financial reporting practices in MFBs. Microfinance institutions should continue to invest in robust corrective and detective controls to enhance their ability to detect and rectify errors and fraudulent activities in financial reporting processes. This investment should include regular reconciliation procedures, comprehensive audits, and the use of advanced fraud detection techniques.